A case‐study on history and rates of gully erosion in Northeast China. (28th July 2021) - Wen, Yanru; Kasielke, Till; Li, Hao; Zepp, Harald; Zhang, Bin
Abstract: Mollisols are of major importance for food security worldwide but are increasingly degraded by soil erosion. Mollisols in Northeast China have been converted into agricultural use only since the 19th century, but gullies are widely distributed. Gully erosion history, rates, and causes in this region remained unclear. We chose a study area with landforms and land‐use history typical for the central Mollisol region of Northeast China to estimate the initiation years and rates of gully erosion from 1968 to 2018 using aerial and satellite imageries. The outlet fan deposits of a large gully system were dated by Cesium‐137 ( 137 Cs) and artifacts. Local farmers were interviewed to verify the results. Gully volumes were measured by a structure‐from‐motion technique using photos taken from an unmanned aerial vehicle. Our results showed that gully systems had already appeared on the steep slopes and along unpaved roads in 1968. They had become larger and more complex in 2018 by the upslope retreat of the main gullies and side gully formation. Gully incision started in the 1950s and 1960s when the original grassland and forest were completely converted into arable land. From 1968 to 2018, the gully density increased from 1.2 to 2.3 km km −2 and the gully heads retreated at speeds from 1.5 to 2.5 m yr −1 . The soil loss from gully erosion ranged from 25.7 to 44.7 Mg yr −1  ha −1 . These data demonstrate the severity of gully erosion in the Mollisol region of Northeast China and underline the importance of appropriate countermeasures.